Incidence and predictive factors of radiation‐induced hypothyroidism in breast cancer patients who receive supraclavicular lymph nodes irradiation: A prospective study. Issue Volume 6:Issues 4(2022) (17th December 2022) - Youssef, Monika; Elmaraghi, Caroline; Kamel, Tarek; El‐Leithy, Mahmoud; Abdelhakim, Khaled
Abstract: Purpose: This paper aimed to assess the incidence of radiotherapy‐induced hypothyroidism (RIHT) in breast cancer patients and correlate it with different factors. Methods: Patients with nonmetastatic breast cancer who received supraclavicular lymph node irradiation as a part of adjuvant radiotherapy from October 2019 to July 2020 were recruited and followed up for 18 months. All patients underwent three‐dimensional conformal radiotherapy and underwent computed tomography simulation. The levels of serum thyroid‐stimulating hormone (TSH), free triiodothyronine and free thyroxine levels were assessed at baseline (before starting radiotherapy) and 9, 12, and 18 months after radiotherapy using immunochemilluminescence. Univariate and multivariate analyses were performed to identify significant factors associated with developing hypothyroidism. Results: Twenty patients out of 96 (20.8%) developed hypothyroidism. Baseline TSH (cutoff value >1.42 μIU/ml) was significantly correlated with hypothyroidism. Conclusion: Routine thyroid function tests assessment is recommended for all breast cancer patients at baseline and after radiotherapy. Abstract :